Numerical simulation of nanofluid convective heat transfer in an oblique cavity with conductive edges equipped with a constant temperature heat source: Entropy production analysis. (1st January 2021) - Tian, Zhe; Shahsavar, Amin; Al-Rashed, Abdullah A.A.A.; Rostami, Sara
Abstract: In the present work, the entropy production of Al2 O3 -water nanofluid in an oblique cavity enclosure is examined. The side edges of the enclosure are at lower temperature and the top and down ones are insulated. Two thick conductive walls are placed on the low temperature edges. Furthermore, the center of the enclosure is equipped with a constant high temperature heat source. The enclosure is exposed to an inclined magnetic field. The governing nonlinear partial differential equations are continuity, Navier–Stokes and energy equations. These equations are solved using an open-source CFD software package (OpenFOAM). The influence of effective parameters includes Ra number, Hartman number, the angles of magnetic field and enclosure, nanoadditives concentration, and aspect ratio on the entropy production and the Bejan (Be) number are investigated. The results show that the minimum entropy production happened at low power magnetic fields. With the increase of the slope of the cavity, the entropy production rises. The addition of nanoadditives leads to an intensification in the entropy production and a reduction in the Be number.